2008
DOI: 10.1017/s0007114508986852
|View full text |Cite
|
Sign up to set email alerts
|

What you think is not what they get: significant discrepancies between prescribed and administered doses of tube feeding

Abstract: Enteral tube feeding remains an indispensible strategy to treat disease-related malnutrition. In the present study we evaluated in clinical practice whether prescribed feeding volumes correspond with administered quantities and we highlight possible causes for discrepancies. During a 4-month observation period data from all patients fully depending on tube feeding (1.5-2.5 litres/d) were collected in a Dutch 900-bed academic hospital. The range for administered feeds to be adequate was set at 100 +/- 10% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 18 publications
3
19
0
2
Order By: Relevance
“…The mean energy balance observed in the present study reached -289.9kcal/day, similar to that found by van den Broek et al. (29) in a study with 55 ward and ICU patients (-259.9kcal/day). This energy deficit is believed to be related to the occurrence of health complications.…”
Section: Discussionsupporting
confidence: 92%
“…The mean energy balance observed in the present study reached -289.9kcal/day, similar to that found by van den Broek et al. (29) in a study with 55 ward and ICU patients (-259.9kcal/day). This energy deficit is believed to be related to the occurrence of health complications.…”
Section: Discussionsupporting
confidence: 92%
“…A study in hospitalised patients found 87% of prescribed tube feedings were met, however this was in a group of patients that were entirely dependent on enteral nutrition (Van den Broek et al , 2009). A systematic review on adherence to prescribed oral nutrition supplements, which is perhaps more akin to the supplementary bolus feeds used in this study, found a mean adherence of 79% (Hubbard et al , 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is clear guidance for protein prescription in UCD, there are surprisingly no publications reporting actual consumption of protein or energy of patient cohorts. It is possible that some patients may under-achieve their prescribed protein intake if they commonly use their protein-free emergency feeds due to illness, experience periodic vomiting, or if they are tube fed [13,14]. Some may consistently over-restrict protein from fear of precipitating hyperammonaemia [5].…”
Section: Dietary Adherencementioning
confidence: 99%